The crystal structure of 7-Bromo-2-(4-chloro-phenyl)-quinoxaline, C14H9BrClN2 - Zhang Lilei; Cheng Tianyu (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C14H8BrClN2, monoclinic, P21/n (no. 14), a = 17.1347(11) Å, b = 3.8441(2) Å, c = 18.4127(12) Å, β = 97.861(2)°, V = 1201.40(13) Å3, Z = 4, Rgt(F) = 0.0388, wRref(F2) = 0.1302, T = 170 K.